Plano de comunicação externa para uma unidade pública de saúde: o caso da Unidade Saúde Escola da UFSCar - Souza, Gisele Catarina Bicaletto de (Universidade Federal de São Carlos, 2020)
This work presents an external communication plan for the Health School Unit (USE) of the Federal University of São Carlos (UFSCar). The plan's proposition was based on an analysis of the strategic field of action in which USE is inserted - the public health network of the Municipality of São Carlos, in São Paulo, and the identification of its actors, and the understanding of their relationships . The theoretical framework presents the main authors of the field theory - Bourdieu, DiMaggio and Fligstein - and also concepts of communication, its relationship with health and the communication plan. The methodology of the work involves a descriptive, exploratory, qualitative research, developed through a Single Case Study, Systematic Bibliographic Review, Content Analysis, and interviews with different actors that make up the USE field. The communication plan proposes actions and products that can be applied by USE in order to consolidate its relationship with the units in the São Carlos network, improve communication between them and, subsequently, obtain more dense resources for the Unit.
External communication plan of a public health unit: the case of the UFSCar Health School Unit
Keywords: Teoria de campo; Campo de ação estratégica; Redes; Redes de Atenção à Saúde; Comunicação; Comunicação em saúde; Plano de comunicação; Field theory; Strategic field of action; Networks; Health care networks; Communication; Health communication; Communication plan; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS